A defense of objectivity in the social sciences, rightly understood. Issue 1 (10th December 2020) - Bird, Frederick
Abstract: In this article, I mount a defense of objectivity as a fitting and necessary norm for the conduct of social scientific research. A number of social scientists and philosophers have criticized this norm because it seems to call for disinterested investigations that are free from any kind of evaluative judgments and seems overwhelmingly to favor quantitative research. I argue that these criteria are inappropriately used as guidelines for objectivity. Researchers can comply with the norm of objectivity, rightly understood, and still be interested observers, make value judgments in relation to their research, and conduct qualitative studies. I argue instead that the norm of objectivity refers to a set of guidelines for interpreting and reporting on research that views this reporting as an intelligible, reasonable, and inherently reciprocating, public activity. By implication these norms also establish correlative guidelines for gathering and analyzing research information. Briefly, as investigators social scientists are called upon honestly to represent our research, to use measures and terms of references that allow for comparisons and verifications by our audiences, and to exercise responsible judgments. I conclude that my account of objectivity is consistent with Weber's defense of this norm more than a century ago.